Implementasi Program Asistensi Mengajar Terhadap Peningkatan Literasi dan Numerasi di MTSS Al-Jamiyatul Chalidiyah Stabat - Ratna Sari, Tri Dessy; Radiyah, Fitra Tur; Peranginangin, Rien Fionita Br; Nazly, Fadhlina (Universitas Nusantara PGRI Kediri, 2025)
Abstract— The implementation of the Teaching Assistance Program aims to improve students' literacy and numeracy at MTSS Al-Jamiyatul Chalidiyah Stabat. This program is part of the Merdeka Belajar Kampus Merdeka (MBKM), which involves university students in school learning activities. Through an approach based on academic mentoring, the use of interactive learning methods, and the integration of educational technology, it is expected to achieve significant improvements in students' reading, writing, and mathematical thinking abilities. The implementation of this program employs observation and interviews as methods for information gathering. The findings indicate that student involvement in learning contributes to an increased understanding of literacy and numeracy materials. With the implementation of the teaching assistance program, students' literacy and numeracy skills have improved, along with the strengthening of interactions among university students, teachers, and pupils, creating a more dynamic learning environment. This initiative recommends further development in program implementation through enhanced training for assisting students, the use of technology-based learning media, and closer collaboration between universities and schools to formulate sustainable learning strategies.